Carotenoids in Skin Photoaging: Unveiling Protective Effects, Molecular Insights, and Safety and Bioavailability Frontiers - Yingchao Ma; Chengxiang Li; Wanping Su; Zhongshi Sun; Shuo Gao; Wei Xie; Bo Zhang; Liying Sui (Antioxidants)
Skin photoaging, driven primarily by ultraviolet radiation, remains a critical dermatological concern. Carotenoids, a class of natural pigments with potent antioxidant properties, have emerged as promising agents for preventing and mitigating photoaging. This review comprehensively integrates current understanding regarding the triggers of skin photoaging, oxidative stress and their associated signal pathways, the photoprotective roles and mechanisms of carotenoids, as well as their bioavailability. Common C40 carotenoids, such as β-carotene, lycopene, astaxanthin, lutein, and zeaxanthin demonstrate remarkable antioxidant activity, primarily attributed to their conjugated double bond structures. Many studies have demonstrated that both oral and topical administration of these C40 carotenoids can effectively alleviate skin photoaging. Specifically, they play a crucial role in promoting the formation of a new skin barrier and enhancing the production of collagen and elastin, key structural proteins essential for maintaining skin integrity and elasticity. Mechanistically, these carotenoids combat photoaging by effectively scavenging reactive oxygen species and modulating oxidative stress responsive signal pathways, including MAPK, Nrf2, and NF-κB. Notably, we also anticipate the anti-photoaging potential of novel carotenoids, with a particular emphasis on bacterioruberin, a C50 carotenoid derived from halophilic archaea. Bacterioruberin exhibits a superior radical scavenging capacity, outperforming the conventional C40 carotenoids. Furthermore, when considering the application of carotenoids, aspects such as safe dosage, bioavailability, and possible long term usage issues, including allergies and pigmentation disorders, must be taken into account. This review underscores the anti-photoaging mechanism of carotenoids, providing strategies and theoretical basis for the prevention and treatment of photoaging.